Anti‐absence activity of mGlu1 and mGlu5 receptor enhancers and their interaction with a GABA reuptake inhibitor: Effect of local infusions in the somatosensory cortex and thalamus. (3rd June 2015) - D'Amore, Valerio; von Randow, Constanze; Nicoletti, Ferdinando; Ngomba, Richard Teke; van Luijtelaar, Gilles
Summary Objective Glutamate and γ‐aminobutyric acid (GABA) are the key neurotransmitter systems in the cortical‐thalamocortical network, involved in normal and pathologic oscillations such as spike‐wave discharges (SWDs), which characterize different forms of absence epilepsy. Metabotropic glutamate (mGlu) and GABA receptors are widely expressed within this network. Herein, we examined the effects of two selective positive allosteric modulators (PAMs) of mGlu1 and mGlu5 receptors, the GABA reuptake inhibitor, tiagabine, and their interaction in the somatosensory cortex and thalamus on SWDs in WAG/Rij rats. Methods Male WAG/Rij rats were equipped with bilateral cannulas in the somatosensory cortex (S1po) or the ventrobasal (VB) thalamic nuclei, and with cortical electroencephalography (EEG) electrodes. Rats received a single dose of the mGlu1 receptor PAM, RO0711401, or the mGlu5 receptor PAM, VU0360172, various doses of tiagabine, or VU0360172 combined with tiagabine. Results Both PAMs suppressed SWDs regardless of the site of injection. Tiagabine enhanced SWDs when injected into the thalamus, but, unexpectedly, suppressed SWDs in a dose‐dependent manner when injected into the cortex. Intracortical co‐injection of VU0360172 and tiagabine produced slightly larger effects as compared to either VU0360172 or tiagabine alone. Intrathalamic co‐injections of VU0360172 and subthreshold doses of tiagabine caused an antiabsence effect similar to that exhibited by VU0360172 alone in the first 10 min. At 30 min, however, the antiabsence effect of VU0360172 was prevented by subthreshold doses of tiagabine, and the combination produced a paradoxical proabsence effect at 40 and 50 min. Significance These data (1) show that mGlu1 and mGlu5 receptor PAMs reduce absence seizures acting at both thalamic and cortical levels; (2) demonstrate for the first time that tiagabine, despite its established absence‐enhancing effect, reduces SWDs when injected into the somatosensory cortex; and (3) indicate that the efficacy of VU0360172 in the thalamus may be critically affected by the availability of (extra)synaptic GABA.